2017
DOI: 10.1007/s00204-017-2077-8
|View full text |Cite
|
Sign up to set email alerts
|

PFOS induces proliferation, cell-cycle progression, and malignant phenotype in human breast epithelial cells

Abstract: Perfluorooctanesulfonic acid (PFOS) is a synthetic fluorosurfactant widely used in the industry and a prominent environmental toxicant. PFOS is persistent, bioaccumulative, and toxic to mammalian species. Growing evidence suggests that PFOS has the potential to interfere with estrogen homeostasis, posing a risk of endocrine-disrupting effects. Recently, concerns about a potential link between PFOS and breast cancer have been raised, but the mechanisms underlying its actions as a potential carcinogen are unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The biological plausibility is supported by limited yet consistent cell‐based mechanistic studies. For instance, the exposure of PFOS at 1–10 μM stimulated in a dose‐dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF‐10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53 . The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co‐exposed to an ER receptor inhibitor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The biological plausibility is supported by limited yet consistent cell‐based mechanistic studies. For instance, the exposure of PFOS at 1–10 μM stimulated in a dose‐dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF‐10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53 . The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co‐exposed to an ER receptor inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, the exposure of PFOS at 1-10 μM stimulated in a dose-dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF-10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53. 23,24 The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co-exposed to an ER receptor inhibitor. On this regard, the authors suggested other alternative mechanisms contributed to explain the effects triggered by PFOS such as the pathway involving the growth factor receptor EGFR/HER2.…”
Section: Modelmentioning
confidence: 95%
“…These features make the MCF-10A a valuable in vitro model for studies of normal breast cell function and determine the potential of environmental contaminants to induce tumor transformation. We have recently demonstrated that PFOS is capable of transforming MCF-10A to a malignant profile by altering important cell cycle proteins as well as inducing cell migration and invasion (Pierozan and Karlsson 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the ability of PFAS to influence cell proliferation, particularly in assays of breast and other endocrine mediated cells and tissues has been assessed. PFOA and PFOS both increased proliferation, cell migration and invasion of normal human breast epithelial cells and altered the expression of proteins involved in cell cycle regulation, including cyclin dependent kinase 4 [202,203]. Similarly, in a mixture with two other chemicals found in consumer products, environmentally relevant concentrations of PFOA increased cell proliferation in non-malignant breast cancer cells through cell cycle disruption, reduced cell apoptosis and increased estrogen receptor alpha levels [204].…”
Section: Alters Cell Proliferation Cell Death or Nutrient Supplymentioning
confidence: 99%
“…PFOA Association: [61] Association: [202]; [204]; [205]; [207]; [209] Long-chain PFAS a PFOS Association: [203]; [207]; [208]…”
Section: Epidemiological Animal Biosassay In Vitromentioning
confidence: 99%